KAJIAN TEKNO-EKONOMI PENDAPATAN USAHA KELAPA DI KABUPATEN MUNA BARAT- SULAWESI TENGGARA - Dhian Herdhiansyah; Iluh Kariasti; La Rianda Asriani (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
The potential for developing coconut commodity plantations in, West Muna Regency, Southeast Sulawesi has not been utilized. This study aims to (a) identify the form and type and capacity of copra business; and (b) knowing the techno- economic study of coconut business revenue located in West Muna Regency, Southeast Sulawesi. Determination of the location of research carried out deliberately (purposive). The method used is a questionnaire and interview. The analysis used is descriptive-analytical and Techno-Economic analysis. The results showed that the form of coconut business in the District of Tiworo Kepulauan Muna Barat Regency is classified as a micro business with assets of 50 million each with a total income in the copra business having a garden of Rp 36.733,125. Then the total coconut business income without processing Rp. 6.493,522 and the total copra business income without having a garden is Rp. 43. 226,647. The total income of copra business in the last 3 years: (a) has the most known plantation income in 2017 amounting to Rp.14,025,625.00; (b) most coconut processing without processing received in 2017 amounted to Rp. 2,390,022.00; and (c) copra business without having the most gardens in 2017 amounted to Rp.16,527,000.00.